Dental caries and associated factors in mothers and their preschool and school children-A cross-sectional study - Alaa Mannaa; Anette Carlén; Peter Lingström (Elsevier, 2013)
Background/purpose: Dental caries remains a major health problem in many parts of the world. The present study aimed at describing the caries experience and caries-related factors in mothers and their preschool and school children. Materials and methods: A sample of 258 individuals (86 mothers and 2 of their children, 4-6 and 12-16 years old) was included. An interview was used to determine the socioeconomic status of the family, oral hygiene, and snacking habits. DMFT /dmft (decayed, missed, filled, teeth), plaque, and gingival indices were recorded. Chair-side tests were used to register salivary buffer capacity and bacterial counts. Results: The caries experience (DMFT/dmft) was high in mothers and their younger and older children (12.4 ± 5.3, 9.0 ± 5.0, and 5.8 ± 4.1, respectively). The DMFT/dmft increased with higher salivary mutans streptococci counts in all age groups (P < 0.05). The caries experiences of the children were correlated positively with those of their mothers (R24-6 = 0.12, R212-16 = 0.18, P < 0.01). A positive association between mothers and both children was evident for toothbrushing habits, snacking frequency, and gingival health (P < 0.05). An association between plaque scores, salivary buffer capacity, and mutans streptococci counts was found between mothers and older children (P < 0.05). Conclusion: The caries experience in Saudi mothers and their children is high, with similar contributory caries-related factors.